Positioning Shifts From Told Self to Performative Self in Psychotherapy - Deppermann, Arnulf; Scheidt, Carl Eduard; Stukenbrock, Anja (Frontiers in Psychology, 2020)
According to Positioning Theory, participants in narrative interaction can position themselves on a representational level concerning the autobiographical, told self, and a performative level concerning the interactive and emotional self of the tellers. The performative self usually is much harder to pin down, because it is a non-propositional, enacted self. In contrast to everyday interaction, psychotherapists regularly topicalize the performative self explicitly. In our paper, we study how therapists respond to clients' narratives by interpretations of the client’s conduct, shifting from the autobiographical identity of the told self, which is the focus of the client’s story, to the present performative self of the client. Drawing on video-recordings from three psychodynamic therapies (tiefenpsychologisch fundierte Psychotherapie) with 25 sessions each, we will analyze in detail five extracts of therapists‘ shifts from the representational to the performative self. We highlight four findings: • Whereas clients’ narratives often serve to support identity-claims in terms of personal psychological and moral characteristics, therapists rather tend to focus on clients’ feelings, motives, current behavior and ways of interacting. • In response to clients’ stories, therapists first show empathy and confirm clients’ accounts, before shifting to clients’ performative self. • Therapists ground the shift to clients’ performative self by references to clients’ observable behavior. • Therapists do not simply expect affiliation with their views on clients’ performative self. Rather they use such shifts to promote the clients’ self-exploration. Yet, if clients resists to explore their selves in more detail, therapists more explicitly ascribe motives and feelings that clients do not seem to be aware of. The shift in positioning levels thus seems to have a preparatory function for engendering therapeutic insights.